2008
DOI: 10.1080/10715760802317655
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, erythrocyte ageing and plasma non-protein-bound iron in diabetic patients

Abstract: Increased oxidative stress and decreased life span of erythrocytes (RBCs) are repeatedly reported in diabetes. In the aim to elucidate the mechanism of the latter, i.e. the events leading to erythrocyte ageing, this study determined in RBCs from diabetic patients iron release in a free desferrioxamine-chelatable form (DCI), methemoglobin (MetHb) formation, binding of autologous IgG to membrane proteins and in plasma non-protein-bound iron (NPBI), F(2)-Isoprostanes (F(2)-IsoPs) and advanced oxidation protein pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The high level of NTBI observed in the diabetes group in this study is in agreement with those of Suleiman et al (2004), Lee et al (2006) and Leoncini et al (2008), but not Van Campenhaut et al (2006). Of the methods used to measure NTBI, HPLC has been suggested to be the 'gold standard' with regard to sensitivity and specificity (Sasaki et al 2011).…”
Section: Accepted Manuscriptsupporting
confidence: 93%
See 1 more Smart Citation
“…The high level of NTBI observed in the diabetes group in this study is in agreement with those of Suleiman et al (2004), Lee et al (2006) and Leoncini et al (2008), but not Van Campenhaut et al (2006). Of the methods used to measure NTBI, HPLC has been suggested to be the 'gold standard' with regard to sensitivity and specificity (Sasaki et al 2011).…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…The study was conducted in accordance with the principles of the Declaration of Helsinki and Committee on the Harmonisation of Good Clinical Practice (Dixon 1999 In support of this calculation, Leoncini et al (2008) reported significant differences in NTBI levels between controls and subjects with diabetes using 24 subjects per group.…”
Section: Subjectsmentioning
confidence: 99%
“…One noteworthy characteristic of diabetes is persistent hyperglycemia, which significantly impairs the oxidant/antioxidant balance by both increasing ROS/RNS and reducing antioxidant levels. Increasing evidence has indicated that oxidative stress contributes to the progression of diabetes and its complications, including skeletal muscle wasting (Aragno et al, 2000;Leoncini et al, 2008). Alternatively, both experimental and clinical studies have demonstrated that enhanced protein breakdown is the most relevant factor in pathological muscle wasting, although inhibitory effects on protein synthesis due to inhibited transport of amino acids into the muscle and repressed mTOR signaling could not be excluded (Costelli and Baccino, 2003).…”
Section: Groupsmentioning
confidence: 96%
“…The ferryl forms tend to undergo synproportionation in presence of ferrous, oxy-forms to the more stable ferric forms (Fe II +Fe IV →2Fe III ) which is longer-lived and hence its likelihood to provide damage are high [8]. Indeed, under a variety of oxidative pathological conditions, ferric RH have been reported to be elevated in blood plasma [9][12].…”
Section: Introductionmentioning
confidence: 99%